Hidrolisado proteico de resíduo de pescado na alimentação da tilápia do Nilo: digestibilidade e desempenho zootécnico - Silva, Thibério Carvalho da (2014)
The aim of this study was to determine the apparent digestibility coefficient (ADC) of energy and nutrients from protein hydrolysate of fish waste (HFW) and the growth performance of larvae of Nile tilapia (Oreochromis niloticus) fed during HFW the sexual reversion. For the digestibility experiment , we used 120 juvenile Nile tilapia with an average weight of 100g, distributed in six tapered cylindrical tanks with a capacity of 90L, suitable for feces, where they remained for a period of seven days to adaptive diets and conditions experimental. The determination ADC and apparent digestible energy were made by indirect method, having been used 0.01% chromic oxide as an inert marker incorporated into the ration. For the performance experiment used 375 larvae were three days old (post-hatching), distributed in 25 aquariums 30L in completely randomized design with five treatments and five replications . Five diets were prepared based on vegetable ingredients, which were included 0, 2, 4, 6 and 8% HFW. The variables analyzed were: final weight, weight gain, specific growth rate, survival and flock uniformity. The digestibility values were: ADC of dry matter, 98.29%; ADC of crude protein, 99.28%; ADC gross energy, 99.13%, and apparent digestible energy of 6425.79 kcal.kg-1. The treatment effect (p<0.05) positively final weight and weight gain, with the best level of 4.75% and the specific growth rate, the best level recorded was 4.77%. We conclude that the HFW can be efficiently used for Nile tilapia. The growth performance was not affected by levels of incluisão HFW, however it is recommended to include 4.75% for this stage of the cultivation of tilapia .